We will how to express the product as a sum or difference.
1. Convert the product into sum or differences: 2 sin 5x cos 3x
Solution:
2 sin 5x cos 3x = sin (5x + 3x) + sin (5x -3x), [Since 2 sin A cos B = sin (A + B) + sin (A - B)]
= sin 8x + sin 2x
2. Express sin (3∅)/2 ∙ cos (5∅)/2 as sum or difference.
Solution:
sin (3∅)/2 cos (5∅)/2
= 1/2 ∙ 2sin (3∅)/2 cos (5∅)/2
= 1/2 [sin ((3∅)/2 + (5∅)/2) - sin ((5∅)/2 - (3∅)/2)]
= 1/2 (sin 4∅ - sin ∅)
3. Convert 2 cos 5α sin
3α into sum or differences.
Solution:
2 cos 5α sin 3α = sin (5α + 3α) - sin (5α -3α), [Since 2 cos A sin B = sin (A + B) - sin (A - B)]
= sin 8α - sin 2α
4. Express the product as a sum or difference: 4 sin 20° sin 35°
Solution:
4sin 20° sin 35° = 2 ∙ 2 sin20° sin 35°
= 2 [cos (35°- 20°) - cos (35° + 20°)]
= 2 (cos 15° - cos 55°).
5. Convert cos 9β cos 4β into sum or differences.
Solution:
cos 9β cos 4β = ½ ∙ 2 cos 9β cos 4β
= ½ [cos (9β + 4β) + cos (9β - 4β)], [Since 2 cos A cos B = cos (A + B) + cos (A - B)]
= ½ (cos 13β + cos 5β)
6. Prove that, tan (60° - ∅) tan (60° + ∅) = (2 cos 2∅ + 1)/(2 cos 2∅ - 1)
Solution:
L.H.S. = tan (60° - ∅) tan (60° + ∅)
= (2 sin (60° - ∅) sin (60° +
∅))/(2cos (60° - ∅) cos (60° + ∅)
= cos [(60° + ∅) - (60° - ∅)] - cos [(60° + ∅)+ (60° - ∅) ]/(cos[(60° + ∅ )+ (60° - ∅) ] + cos [(60° + ∅) - (60° - ∅) ] )
= (cos 2∅ - cos 120°)/(cos 120° + cos 2∅)
= (cos 2∅ - (-1/2))/(-1/2 + cos 2∅), [Since cos 120° = -1/2]
= (cos 2∅ + 1/2)/(cos 2∅ - 1/2)
= (2 cos 2∅ + 1)/(2 cos 2∅ - 1) proved
7. Convert the product into sum or differences: 3 sin 13β sin 3β
Solution:
3 sin 13β sin 3β = 3/2 ∙ 2 sin 13β sin 3β
= 3/2 [cos (13β - 3β) - cos (13β + 3β)], [Since 2 sin A sin B = cos (A - B) - cos (A + B)]
= 3/2 (cos 10β - cos 16β)
8. Show that, 4 sin A sin B sin C = sin (A + B - C) + sin (B + C - A) + sin (C+ A - B) - sin (A + B + C)
Solution:
L.H.S. = 4 sin A sin B sin C
= 2 sin A (2 sin B sin C)
= 2 sin A {cos (B - C) - cos (B + C)}
= 2 sin A ∙ cos (B - C) - 2 sin A cos (B + C)
= sin (A + B - C) + sin (A - B + C) - [sin (A + B + C) - sin (B + C -A)]
= sin (A + B - C) + sin (B + C - A) + sin (A + C - B) - sin (A + B + C) = R.H.S.
Proved
● Converting Product into Sum/Difference and Vice Versa
11 and 12 Grade Math
From Express the Product as a Sum or Difference to HOME PAGE
Didn't find what you were looking for? Or want to know more information about Math Only Math. Use this Google Search to find what you need.
Sep 19, 24 12:56 AM
Sep 18, 24 03:29 PM
Sep 18, 24 02:47 PM
Sep 17, 24 01:47 AM
Sep 17, 24 12:10 AM
New! Comments
Have your say about what you just read! Leave me a comment in the box below. Ask a Question or Answer a Question.